Sovereign collateral as a Trojan Horse: Why do we need an LCR+ - Buschmann, Christian; Schmaltz, Christian (Journal of Financial Stability, 2017)
Sovereign bonds are widely used as collateral in banks’ funding and trading operations. If a sovereign becomes distressed, the collateral mechanism impairs and banks are suddenly facing significant liquidity calls. Basel III's Liquidity Coverage Ratio (LCR) protects banks against unexpected liquidity calls, but currently excludes sovereign distress. Thus, all banks fulfilling the LCR are still exposed to a liquidity risk stemming from distressed sovereign debt and materializing through the collateral channel. Our paper shows that this unaddressed risk can translate into a system-wide liquidity shock. To gauge the potential damage caused by such a shock, we develop a model based on banks’ home sovereign exposures and a bundle of simplifying assumptions in which sovereign distress triggers bank distress. Our model describes how deteriorating sovereign collateral can lead to an overall liquidity squeeze and non-compliance with Basel III liquidity standards. As this risk is too material to be neglected, we propose an alternative version of the LCR, LCR+, which includes the liquidity impact of sovereign distress.